2020
DOI: 10.3390/jcm9051460
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Spaces of the Female Pelvis—Clinical Applications in Obstetrics and Gynecology

Abstract: The term “spaces” refers to the areas delimited by at least two independent fasciae and filled with areolar connective tissue. However, there is discrepancy regarding the spaces and their limits between clinical anatomy and gynecologic surgery, as not every avascular space described in literature is delimited by at least two fasciae. Moreover, new spaces and surgical planes have been developed after the adoption of laparoscopy and nerve-sparing gynecological procedures. Avascular spaces are useful anatomical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 41 publications
0
42
0
2
Order By: Relevance
“…In another study of this region, Kostov et al (2020) described the region between the urinary bladder and the vagina as the vesicovaginal space–one of nine avascular spaces in the female pelvis. Considering that two of the dissections in our study found the VVF to be a double layer of fascia, it may be possible that the avascular space described by Kostov et al (2020) correlates with the apparently avascular plane found between these two layers. Greater clarification for this layered arrangement is needed and will require further histological studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of this region, Kostov et al (2020) described the region between the urinary bladder and the vagina as the vesicovaginal space–one of nine avascular spaces in the female pelvis. Considering that two of the dissections in our study found the VVF to be a double layer of fascia, it may be possible that the avascular space described by Kostov et al (2020) correlates with the apparently avascular plane found between these two layers. Greater clarification for this layered arrangement is needed and will require further histological studies.…”
Section: Discussionmentioning
confidence: 99%
“…26 The internal iliac artery lies below the external iliac vein and most of the endoscopists start performing the laparoscopic standard transperitoneal lymphadenectomy over the external iliac vein and then open the paravesical/pararectal spaces for pelvic lymph node dissection. 27,28 In our technique, the paravesical/pararectal spaces were being exposed at the beginning of retroperitoneal dissection and prophylactic ligation of UA at its origin was administered. The laparoscopic standard transperitoneal lymphadenectomy over the external iliac vein performed after first attempting prophylactic ligation of UA at its origin.…”
Section: Discussionmentioning
confidence: 99%
“…Некоторые пространства используются для проведения оперативных вмешательств влагалищным доступом [7]. Стоит заметить, что в зависимости от нозологии используются различные доступы к клетчаточным пространствам женского таза [8,9]. Названия пространств происходят от наименований органов, окружающих их [8].…”
Section: результаты исследования и их обсуждениеunclassified
“…Последними исследованиями было доказано наличие нескольких фасциальных слоев внутри пространства Ретциуса, поэтому не совсем верно считать его единым анатомическим образованием [29]. Вдоль передней поверхности мочевого пузыря к пупку тянется пузырнопупочная или предпузырная фасция [9]. Задняя поверхность лобкового симфиза покрыта париетальной фасцией таза, которая является продолжением книзу поперечной фасции [2,10].…”
Section: результаты исследования и их обсуждениеunclassified